2018
DOI: 10.1080/17429145.2018.1472308
|View full text |Cite
|
Sign up to set email alerts
|

Modern plant cultivation technologies in agriculture under controlled environment: a review on aeroponics

Abstract: This review paper describes a novel approach to plant cultivation under soil-less culture. At present, global climate change is expected to raise the risk of frequent drought. Agriculture is in a phase of major change around the world and dealing with serious problems. In future, it would be difficult task to provide a fresh and clean food supply for the fast-growing population using traditional agriculture. Under such circumstances, the soil-less cultivation is the alternative technology to adapt effectively.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
151
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 192 publications
(158 citation statements)
references
References 97 publications
(95 reference statements)
0
151
0
7
Order By: Relevance
“…Their study reports concluded that it could be well accepted in agriculture as a modern-day plant cultivation activity where the modern farmer does not need soil to grow the plant. However, the aeroponic system has some substantial vulnerability like a failure of water supply pumps, nutrient distribution line and preparation, and atomization nozzle clogging, which require special knowledge and attention to avoid damage, rapid plant death, and failure of the system [23]. Furthermore, the integration of the intelligent agriculture techniques could be the best solution to avoid or deal with the abovementioned issues without any technical expertise.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Their study reports concluded that it could be well accepted in agriculture as a modern-day plant cultivation activity where the modern farmer does not need soil to grow the plant. However, the aeroponic system has some substantial vulnerability like a failure of water supply pumps, nutrient distribution line and preparation, and atomization nozzle clogging, which require special knowledge and attention to avoid damage, rapid plant death, and failure of the system [23]. Furthermore, the integration of the intelligent agriculture techniques could be the best solution to avoid or deal with the abovementioned issues without any technical expertise.…”
Section: Related Workmentioning
confidence: 99%
“…Moreover, several studies considered aeroponics as a modern-day agricultural activity which is practiced in an enclosed growth chamber under entire controlled conditions, as it could eliminate the external environmental factors as compared with traditional agriculture activity. Hence, it is no longer dependent on large-scale land use, and it could be set up in any place, a building that has lifted global climate without considering the current climate such as rainy season and winter [23,[55][56][57][58][59]. Buer et al [60] reported that atomization nozzle uses the tiny amount of the water nutrient solution and provides an excellent growth environment for the plant.…”
Section: The Aeroponic Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Droplet sizes larger than 100 mm tend to fall faster and generate less oxygen in the root zone environment (Gopinath et al, 2017;Morgan, 2005). Conversely, very small droplet sizes promote excessive growth of root hairs and may compromise the production of minitubers (Buckseth et al, 2016;Chiipanthenga et al, 2012;Gopinath et al, 2017;Lakhiar et al, 2018;Stoner and Clawson, 1998). Problems for optimization of aeroponics systems can arise due to the droplet size of the misting nozzle as well as the interval and duration time of the nutrient solution spray (Clawson et al, 2000).…”
Section: Resultsmentioning
confidence: 99%
“…Aeroponics is a soil-less cultivation system considered a specialized version of hydroponics [34]. It is an air-water system in which the roots of the plant extend and grow inside a closed container in the dark, are exposed to air, and directly sprayed with a nutrient-water mix through atomizers (Figure 1).…”
Section: Resultsmentioning
confidence: 99%